Cutting Characteristics of a Ductile Rock - YASAR, Serdar (GeoScience Engineering, 2020)
A rock sample was obtained from an underground lignite mine for the investigation of the cutting characteristics of a ductile rock where the heading is achieved with a roadheader. The rock sample (metasiltstone) was classified according to a pertinent brittleness classification by means of its compressive strength to tensile strength ratio. Two types of drag picks are used for the execution of the experimental campaign on core and block samples of the metasiltstone. The cutting force, the specific energy and the breakout angle variables were investigated. The cutting force-distance histories of cutting trials were compared with the present literature. It was seen that even an extremely ductile rock sample exhibited the characteristics of brittle cutting regime. Keywords: Brittleness; Brittle regime; Cutting mode; Ductile regime; Roadheaders; Rock cutting. DOI 10.35180/gse-2020-0033